2005
DOI: 10.1542/peds.2004-0845
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and Clinical Responses to Rituximab in a Child With Opsoclonus-Myoclonus Syndrome

Abstract: ABBREVIATIONS. OMS, opsoclonus-myoclonus syndrome; CSF, cerebrospinal fluid; NK, natural killer; IVIg, intravenously administered immunoglobulin; Ig, immunoglobulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 25 publications
1
25
0
6
Order By: Relevance
“…IgG and IgA titers showed no statistically significant changes [Pranzatelli et al 2006]. Other case reports also confirm the benefit of rituximab in OMS children including a 3½-year-old patient with ganglioneuroblastoma [Bell et al 2008;Burke and Cohn, 2008;Corapcioglou et al 2008;Pranzatelli et al 2005].…”
Section: Opsoclonusmyoclonus Syndromementioning
confidence: 91%
“…IgG and IgA titers showed no statistically significant changes [Pranzatelli et al 2006]. Other case reports also confirm the benefit of rituximab in OMS children including a 3½-year-old patient with ganglioneuroblastoma [Bell et al 2008;Burke and Cohn, 2008;Corapcioglou et al 2008;Pranzatelli et al 2005].…”
Section: Opsoclonusmyoclonus Syndromementioning
confidence: 91%
“…Pranzatelli et al further reported response to treatment with rituximab which is an anti-CD 20 monoclonal antibody. The clinical improvement correlated with reduction of B lymphocytes in CSF 3335…”
Section: Pathology and Pathogenesismentioning
confidence: 81%
“…Em alguns casos, há necessidade de manutenção da terapia por vários meses (19) . A gamaglobulina intravenosa, a azatioprina, a ciclosfosfamida, as sessões de plasmaferese e, recentemente, o rituximabe são alternativas terapêuticas para casos refratários (2,9,23,24) . Em nosso meio, essas alternativas terapêuticas ainda são limitadas.…”
Section: Discussionunclassified